Cost accounting : using a cost management approach - Rayburn, Letricia Gayle. (Irwin, 1996)
Cost/management accounting concepts. Product cost allocation and accumulation procedures. Cost data for performance evaluation. Cost planning and control. Cost accounting/cost management for decision making. Analysis of costs and profits.